ANALISIS INTERAKSI SOSIAL PESERTA DIDIK KELAS VIII SMP NEGERI 10 PONTIANAK - Agstria, Wiwil Cristin; Astuti, Indri; Purwanti, Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to analyze the interaction of eighth grade students of SMP Negeri 10 Pontianak. The form of research is a survey study with descriptive method which is a research method that reveals problems at the time this research is conducted. The sample of this study was grade VIII students of Pontianak State Junior High School. The data collection techniques used in this study are indirect communication techniques, namely data collection techniques carried out directly against respondents using an intermediary tool in the form of a questionnaire in the form of multiple choices totaling 45 items after 50 items were validated before being tested for validity and communication techniques. directly yaiut data collection techniques carried out by way of face-to-face with research respondents in the form of interviews. Based on the results of the analysis of the data that has been studied shows that the social interaction of VIII grade students reached 78.40% in the Good category. This shows that the social interactions that exist in class VIII SMP Negeri 10 Pontianak both when interacting with the teacher and when interacting with school friends are fairly good.Â Keyword: Analysis, Interaction, Social